ДОСЛІДЖЕННЯ ВПЛИВУ ТЕРМОДИНАМІЧНИХ ПРОЦЕСІВ НА РОБОТУ СИНУСНОГО ВУЗЛА СЕРЦЕВО-СУДИННОЇ СИСТЕМИ - Стенцель, Й. І.; Кожем'яко, В. П.; Петросян, Л. І. (Vinnytsia National Technical University, 2014)
The investigation of thermodynamic phenomena in the human bodywhich are caused by biochemical and heat exchange processes . It is shown that the process of heat transfer through the cardiovascular system is the vibrational amplitude is determined by the temperature of the biochemical changes and natural frequency - the heart, the condition of the vascular system and heat transfer process in the environment. It is shown that the natural frequencies heat - and mass transfer in the normal state of the organism are synchronized both temperature and time . If you violate synchronization diseases arise due to the frequency of the beating , leading to drastic temperature changes.